Biological and Social Impacts of Implementing Artificial Intelligence-Based Economic Policies: A Discourse Analysis - De-Veer, Theodora Pearl; Akwetey, George; Sentre, Justa (Yayasan Ilomata, 2025)
Introduction/Main Objectives: This manuscript investigates the biological and social ramifications of AI-powered economic policies, aiming to elucidate the multifaceted impacts of artificial intelligence on societal structures and health outcomes. Background Problems: The rapid integration of AI technologies into economic frameworks raises critical ethical concerns, including algorithmic bias and accountability, which can exacerbate existing social inequalities. Additionally, the implications for human-AI interaction in healthcare settings necessitate a deeper understanding of how these technologies affect patient outcomes and clinician practices. Methods: A discourse analysis was conducted on ten peer-reviewed articles, focusing on themes such as ethical accountability, human-AI interaction, social equity, and workforce dynamics. Findings: The analysis revealed four primary themes: (1) Ethical and Accountability Challenges, highlighting the necessity for robust frameworks to address algorithmic bias; (2) Human-AI Interaction and Its Biological Implications, emphasizing the need for clinician training and AI literacy; (3) Social Equity and Access Issues, underscoring the risk of exacerbating existing disparities; and (4) Economic Impact and Workforce Dynamics, pointing to the dual-edged nature of AI's integration into economic policies. Conclusions: The findings underscore the imperative for policymakers to develop ethical guidelines and promote AI literacy while implementing strategies for workforce reskilling. By addressing these challenges, society can harness the transformative potential of AI technologies while safeguarding social equity and enhancing health outcomes.